Lecturers and students’ perceptions about online learning problems during the COVID-19 pandemic - Sri Marmoah; Jenny Indrastoeti Siti Poerwanti (Journal of Education and Learning (EduLearn), 2022)
This research is based on the problem of the outbreak of the coronavirus which has become a global pandemic and a national disaster. The purpose of this study was to describe the perceptions of lecturers and students on online learning problems during the COVID-19 pandemic. The data was collected with the help of questionnaires. This quantitative descriptive study was conducted among lectures and students who selectedd randomly. Data analysis used a Likert scale and the results of perceptions used descriptive analysis. The results of the study show that the perceptions of lecturers and students on online learning problems during the pandemic consisted of six aspects (lecture plans, online lecture activities, online lecture recording and evaluation, lecture assistance services, and lecture support facilities). Furthermore, it can be agreed that effective online learning occurs due to the interaction of students and lecturers as well as technology connected to education.